'Stat' workflow modifications to expedite care after needlestick injuries. (5th January 2021) - Smith, J L; Banerjee, R; Linkin, D R; Schwab, E P; Saberi, P; Lanzi, M
Abstract: Background: Post-exposure prophylaxis (PEP) for human immunodeficiency virus (HIV) is recommended to start within hours of needlestick injuries (NSIs) among healthcare workers (HCWs). Delays associated with awaiting the results of testing from the source patient (whose blood was involved in the NSI) can lead to psychological consequences for the exposed HCW as well as symptomatic toxicities from empiric PEP. Aims: After developing a 'stat' (immediate) workflow that prioritized phlebotomy and resulting of source patient bloodwork for immediate handling and processing, we retrospectively investigated whether our new workflow had (i) decreased HIV order-result interval times for source patient HIV bloodwork and (ii) decreased the frequency of HIV PEP prescriptions being dispensed to exposed HCWs. Methods: We retrospectively analysed NSI records to identify source patient HIV order-result intervals and PEP dispensing frequencies across a 6-year period (encompassing a 54-month pre-intervention period and 16-month post-intervention period). Results: We identified 251 NSIs, which occurred at similar frequencies before versus after our intervention (means 3.54 NSIs and 3.75 NSIs per month, respectively). Median HIV order-result intervals decreased significantly ( P < 0.05) from 195 to 156 min after our intervention, while the proportion of HCWs who received one or more doses of PEP decreased significantly ( P < 0.001) from 50% (96/191) to 23% (14/60). Conclusion: Using a 'stat' workflow to prioritize source patient testing after NSIs, we achieved a modest decrease in order-result intervals and a dramatic decrease in HIV PEP dispensing rates. This simple intervention may improve HCWs' physical and psychological health during a traumatic time.